Collegial Organizational Climate Alleviates Japanese Schoolteachers’ Risk for Burnout - Hashimoto, Hirofumi; Maeda, Kaede (Frontiers in Psychology, 2021)
The purpose of the current study was to examine the influence of individuals’ help-seeking preferences and their collective perception of the organizational climate in school on teachers’ mental health. Previous studies demonstrated that help-seeking preference was negatively associated with the risk of burnout, suggesting that teachers who hesitate to seek help from their colleagues are more inclined to have mental health problems. Thus, the current study hypothesized that a collegial organizational climate would be negatively associated with burnout. To test this hypothesis, we developed a scale to measure schoolteachers’ collective perception of their organizational climate (Study 1), and the newly developed scale was used to assess its relationship with help-seeking preferences and teachers’ burnout risk (Study 2). The results demonstrated that younger teachers, a low level of help-seeking, and a less collaborative climate increased the risk of burnout. The results also showed a significant interaction effect, indicating that help-seeking preference was less closely associated with teachers’ burnout risk if their organization was perceived as having a collegial climate. These findings clearly show how the social environment of a school’s organizational climate can affect schoolteachers’ mental health in Japan.